Pratiques langagières, contextes d’interaction et genres de discours en logopédie / orthophonie - Weck, Geneviève de (Travaux neuchâtelois de linguistique, 2003)
The article’s aim is to analyze the language practices from logopedic interventions, realized under dialogs. The frequent opposition between structured activities and spontaneous speech is criticized, and replaced by the notion of discourse heterogeneous dialog. The dialogs’ analyze is based on conversational analysis and discourse interactionism principles. 3 levels of dialogs’ management are distinguished: the management of interaction (turn takings, topics, conversational breakdowns, etc.), the management of discourse (ancorage, planification, textualization) and the verbal scaffolding (adults’ strategies, children’s reactions). Two examples of dialog between a speech therapist and a child are studied. They show the heterogeneousness of discourses produced by the interlocutors: many sequences and sub-sequences are highlighted.